Knowledge and communication needs assessment of community health workers in a developing country: a qualitative study - Hafeez Assad; Haq Zaeem (BMC, 2009)
Abstract Background Primary health care is a set of health services that can meet the needs of the developing world. Community health workers act as a bridge between health system and community in providing this care. Appropriate knowledge and communication skills of the workers are key to their confidence and elementary for the success of the system. We conducted this study to document the perceptions of these workers on their knowledge and communication needs, image building through mass media and mechanisms for continued education. Methods Focus group discussions were held with health workers and their supervisors belonging to all the four provinces of the country and the Azad Jammu & Kashmir region. Self-response questionnaires were also used to obtain information on questions regarding their continued education. Results About four fifths of the respondents described their communication skills as moderately sufficient and wanted improvement. Knowledge on emerging health issues was insufficient and the respondents showed willingness to participate in their continued education. Media campaigns were successful in building the image of health workers as a credible source of health information. Conclusion A continued process should be ensured to provide opportunities to health workers to update their knowledge, sharpen communication skills and bring credibility to their persona as health educators.